A clash of conventions? Participation, power and the rights of disabled children - Sandland, Ralph (Cognatio Press, 2017)
This paper considers the neglected topic of the relationship between the Convention on the Rights of Persons with Disabilities and the Convention on the Rights of the Child, with regard to the participation rights of disabled children. It analyses key articles in both conventions and considers relevant General Comments from both convention committees (the Committee on the Rights of the Child or ‘CCRC’ and the Committee on the Rights of Persons with Disabilities or ‘CCRPD’), and their interpretation by academic contributors. The paper argues that much work on this topic fails to develop an adequate 16 understanding of power relations, and that the ‘social model of disability’ which underpins the disabilities convention, when applied to ‘childhood’ (as opposed to ‘children’) suggests that the implications of that convention for the participation rights of all children, not only disabled children, are profound. This is because the disabilities convention rejects the relevance of tests of capacity and ‘best interests’ for disabled adults, for reasons which are equally germane to disabled children, and children in general. The paper concludes with discussion of the difficulties in implementing the insights derived from the analysis of the disabilities convention in substantive law in the absence of a right to freedom from age discrimination for children, and suggests other, less far-reaching, reforms that could be made this notwithstanding.